2013
DOI: 10.1080/07481187.2012.722041
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of “Primary Bereavement Care” for Widows: A Cluster Randomized Controlled Trial Involving Family Physicians

Abstract: Thirty-one family physicians, from 19 primary care teams in Biscay (Spain), were randomly assigned to intervention or control group. The 75 intervention family physicians, after training in primary bereavement care, saw 43 widows for 7 sessions, from the 4th to 13th month after their loss. The 16 control family physicians, without primary bereavement care training, saw 44 widows for 7 ordinary appointments, with the same schedule. Outcome measures were collected at 4, 10, 16, and 24 months after the loss. A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…A consequence of this complex symptom profile is that those with CG may be inappropriately diagnosed and treated, perhaps to control the intense emotions in the early stages of bereavement ( García et al, 2013 ; García and Landa, 2015 ), leading to later difficulties with grief resolution. This is an under-investigated topic, though in one qualitative study of bereaved mothers, all showed remorse that their medication schedule did not allow them to fully experience loss-related feelings ( Bosquet-del Moral et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A consequence of this complex symptom profile is that those with CG may be inappropriately diagnosed and treated, perhaps to control the intense emotions in the early stages of bereavement ( García et al, 2013 ; García and Landa, 2015 ), leading to later difficulties with grief resolution. This is an under-investigated topic, though in one qualitative study of bereaved mothers, all showed remorse that their medication schedule did not allow them to fully experience loss-related feelings ( Bosquet-del Moral et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on this topic were conducted outside of the U.S. and provide some suggestions of how training might be implemented, with one testing the efficacy of informational pamphlets and brief training on primary care physicians in Denmark (Guldin, et al ., 2013), and the other, conducted in Spain, randomly assigning family physicians to either receive training in bereavement care or to no training (Garcia, et al ., 2013). No significant changes were found in patient grief symptoms in either study, however.…”
Section: Resultsmentioning
confidence: 99%
“…There were no differences between intervention [information pamphlet (Guldin, Vedsted, Jensen et al, 2013) or structured PBC (Garcia, Landa, Grandes et al, 2013)], and control groups [usual care (Guldin et al, 2013;Garcia et al, 2013)]. Bereaved people improved through time in both the intervention and control groups.…”
Section: Randomized Control Trials In Primary Be-reavement Carementioning
confidence: 90%
“…In conclusion, an ideal bereavement intervention model in PC would use FPs trained in basic bereavement care, willing to discuss feelings with bereaved people, and using a less structured intervention; minimal and natural responsiveness in cases of normal grief (REFINO), deeper intervention in high risk cases, and much deeper in complicated grief, where referral to a mental health specialist could be indicated (García, Landa, Grandes et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation